RESENTRALISASI PERIZINAN BERUSAHA PERTAMBANGAN MINERAL DALAM UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Sanduan, Akbar Prasetyo (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The division of concurrent government affairs in terms of licensing of mineral and coal mining businesses in their development has been degraded as a result of the establishment of Law No. 11 of 2020 concerning Job Creation. The reduced concurrent government affairs illustrate the desire of the central government to decentralize government affairs, even though ideally the authority to distribute concurrent government affairs is an authority that should be the jurisdiction of local governments. This research is legal research. The problem approach used to answer the legal issues of this research is the statutory approach, which is an approach that uses statutory regulations. Next is the conceptual approach used to examine and analyze the framework of thought, conceptual framework, or juridical basis. From the approach used, the researcher can use an analytical knife in finding answers to the legal issues of writing this thesis. Based on the analysis of legal materials, it can be concluded that the recentralization of licensing arrangements conflicts with the principle of Regional Autonomy because First, there is a conflict of norms against the provisions in Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Second, it is not under the principle of division of affairs. Governance, namely accountability, externalities, efficiency, and national strategic interests. The suggestion that can be given is that the DPR together with the President revise Article 402 A of Law No. 11 of 2020 concerning Job Creation which in this provision is contrary to the principle of regional autonomy.